Terobosan Pemikiran Islam Menembus Kesadaran: Menafsiri Liberasi Pemikiran ala Ibnu Rusyd - Nur Ihsan Shaleh (Sekolah Tinggi Agama Islam (STAI) Khozinatul Ulum Blora, 2018)
Ibnu Rusyd was a phenomenal figure in his day, this character was able to master the theories of various scientific disciplines and at the same time he has applied them. Appart from that, his efforts to rationalize religious theachings to be accepted are always sought. So it is not strange if the rationality has brough by him can be accepted by society. This statement has strong reasons for the existence of his work which focuses on the teachings of fiqh nuanced social worship. This book which has four schools has a direction to provide solutions to developing problems. From this design, at least Ibnu Rusyd wants to give something that foam is used by general public, so that his efforts to learn various sciences such as philosophy, medicine, psychology, fiqh, social society an so on can be given to people who need it. In addition, the breakthrough pattern of thought that he uses is able to penetrate the consciousness that has been built up so far. The liberation of thought that he uses feels moderate and easily accepted by ordinary people or educate people.